The Indonesian National Sports Games (PON): Expectations and Reality - Ma'mun, Amung (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
This paper describes an empirical study about the expectation and reality of the Indonesian NationalSportsGames (PON) aftertheregulationaboutnationalsportsystemcameintoforce in 2005. To describe the achievement and issues associated with the objectives of PON, analyses of report documents of the 2008, 2012, and 2016 PON were carried out. In addition, interviews with athletes and officials from several contingents and focus group discussions with experts were also conducted. In terms of maintaining the unity and integrity of the nation, PON could be deemed to meet the expectations but some modifications should be made to the idealism, management, andsport contents to improve the development system of national sport. However, organizing PON as a talent scout effort is no longer valid due to some issues associated with recruitment system, match and sport categorization system, and event time selection. Even so, PON is still needed to stimulate sport development in regional level. There should be a new policy in order for PON to achieve all of its goals.